Controllable Skyrmionic Phase Transition between Néel Skyrmions and Bloch Skyrmionic Bubbles in van der Waals Ferromagnet Fe3‐δGeTe2 - Chen Liu; Jiawei Jiang; Chenhui Zhang; Qingping Wang; Huai Zhang; Dongxing Zheng; Yan Li; Yinchang Ma; Hanin Algaidi; Xingsen Gao; Zhipeng Hou; Wenbo Mi; et al. (Advanced Science, 2023)
Abstract The van der Waals (vdW) ferromagnet Fe3‐δGeTe2 has garnered significant research interest as a platform for skyrmionic spin configurations, that is, skyrmions and skyrmionic bubbles. However, despite extensive efforts, the origin of the Dzyaloshinskii–Moriya interaction (DMI) in Fe3‐δGeTe2 remains elusive, making it challenging to acquire these skyrmionic phases in a controlled manner. In this study, it is demonstrated that the Fe content in Fe3‐δGeTe2 has a profound effect on the crystal structure, DMI, and skyrmionic phase. For the first time, a marked increase in Fe atom displacement with decreasing Fe content is observed, transforming the original centrosymmetric crystal structure into a non‐centrosymmetric symmetry, leading to a considerable DMI. Additionally, by varying the Fe content and sample thickness, a controllable transition between Néel‐type skyrmions and Bloch‐type skyrmionic bubbles is achieved, governed by a delicate interplay between dipole–dipole interaction and the DMI. The findings offer novel insights into the variable skyrmionic phases in Fe3‐δGeTe2 and provide the impetus for developing vdW ferromagnet‐based spintronic devices.